Topographic and morphometric characteristics of human renal pyramids of the upper end at mature and elderly ages - Dudenko, V. G.; Vdovichenko, V. I. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. New endoscopic methods of surgical treatment of kidney diseases still cause complications and require further deepening and generalization of knowledge about the peculiarities of the topographic and anatomical structure of the human kidney. Methods.150 human kidneys were taken from patients of both sexes at mature and elderly age died after accidents or diseases not associated with the pathology of urinary system. Next indicators of renal pyramids were examined: diameter of the base of renal pyramid, the diameter of the renal papilla, height of renal pyramids, and volume of renal pyramids. Standard methods of anatomical study were used: preparation, macroscopy, morphometry of native kidneys, morphometry of renal pyramids in upper end based on plane-parallel topographical anatomical sections of kidney, comparative digital morphometry based on digital calibrated plane-parallel topographical anatomical sections of the upper end of the kidney, statistical processing and mathematical analysis of the data. Results. It was measured 634 pyramids in the upper end of 150 kidneys. There were found from 3 to 8 renal pyramids in the upper end of each kidney, an average of 4.22±0.15. All pyramids were structurally divided into two groups: 1) single (solitary), which independently form the renal papilla and drain into a minor renal calyces; 2) group (fusion), a compound of two or more single renal pyramids or large renal pyramids that looked separated, since the renal papilla. Number of single renal pyramids was from 3 to 8, on average (4.0±0.54). Number of group renal pyramids was from 0 to 4, an average (2.0 ± 0,65). Constant superior medial pyramid (pms) - the largest significantly more than any other pyramids for all measured parameters (diameter of the base, the diameter of the renal papilla, height and volume of the pyramid). Commonly found superior lateral pyramid (pls) – has less than the previous in diameter of the base, the diameter of the renal papilla and height, but more in height. Superior anterior pyramid (pas) and superior posterior pyramid (pps) – commonly found, all parameters less than the previous two pyramids, average values of parameters differ slightly. Anterior superior lateral pyramid (plsa) and posterior superior lateral pyramid (plsp) - rare pyramids, all parameters less than the previous two pyramids, average values of the parameters differ slightly. Anterior superior medial pyramid (pmsa) and posterior superior medial pyramid (pmsp) - rare pyramids, all parameters less than the previous two pyramids, the average values of the parameters differ slightly. Conclusion. It is perspective to study the topography of the upper end of the human renal pyramids on the basis of the proposed classification, based on their location in relation to the renal sector and parallels. Also, the classification of the pyramids, tied to small renal cups can also be used for other parts of the kidney.